Handling heterogeneity in English geography textbooks 1850–2000. Issue 5 (3rd September 2017) - Taylor, Liz
Abstract: Teaching demands engagement with a diverse world. When teaching about distant places, school textbooks commonly employ mediation devices of comparison, contrast and narratives of change. To what extent are such pedagogical strategies inherently othering? This question is addressed in the context of representations of Japan in English geography textbooks from 1850 to 2000. A process of detailed qualitative analysis was applied to the books, focussing on language structures, but also considering visual elements. Although the nature of comparison and change narratives varied over time, there was an enduring power dynamic within their construction. It is important to recognize this dynamic because of the widespread use of such taken-for-granted strategies. This is relevant not only to geography education but to any discipline in which the world is represented. Can other ways of constructing the world offer an alternative approach?